2023
DOI: 10.1088/1361-6641/acbb1e
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Schottky barrier in a graphene/AlP van der Waals heterostructure

Abstract: The controllable modulation of the electronic properties of two-dimensional van der Waals (vdW) heterostructures is crucial for their applications in the future nanoelectronic and optoelectronic devices. In this paper, the electronic properties of a graphene/AlP heterostructure are theoretically studied by first-principles calculation. The results show that due to the weak vdW interaction between graphene and the AlP monolayer, both the Dirac semi-metallic properties of graphene and the semiconductivity proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This compound has a wide indirect band gap of 2.45 eV and a unit cell parameter of 5.47 Å . AlP is an important component in the development of optoelectronic and transfer-electron devices. , Also, in their bulk form, it has been employed in the manufacturing of photodetectors and light-emitting diodes. , Moreover, theoretical studies have demonstrated that AlP impurified with vanadium acquires ferromagnetic characteristics with half-metal properties, which become suitable for spintronic applications . AlP presents a structural transition from zinc-blende to NiAs-type structure under high pressure at a transition pressure of 9.5 GPa .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound has a wide indirect band gap of 2.45 eV and a unit cell parameter of 5.47 Å . AlP is an important component in the development of optoelectronic and transfer-electron devices. , Also, in their bulk form, it has been employed in the manufacturing of photodetectors and light-emitting diodes. , Moreover, theoretical studies have demonstrated that AlP impurified with vanadium acquires ferromagnetic characteristics with half-metal properties, which become suitable for spintronic applications . AlP presents a structural transition from zinc-blende to NiAs-type structure under high pressure at a transition pressure of 9.5 GPa .…”
Section: Introductionmentioning
confidence: 99%
“…13 AlP is an important component in the development of optoelectronic and transfer-electron devices. 14,15 Also, in their bulk form, it has been employed in the manufacturing of photodetectors and light-emitting diodes. 16,17 Moreover, theoretical studies have demonstrated that AlP impurified with vanadium acquires ferromagnetic characteristics with half-metal properties, which become suitable for spintronic applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Together with the rise of two-dimensional (2D) materials starting from the discovery of graphene, [14][15][16][17] 2D magnetic materials with intrinsic magnetism are successively proposed theoretically or synthesized experimentally, such as Gr 2 Ge 2 Fe 6 , CrI 3 , VSe 2 , CrGeTe 3 , Fe 3 GeTe 2 , NiPS, CoH 2 , CrBr 3 , etc. [18][19][20][21][22][23][24][25][26][27] More interestingly, some 2D materials, such as graphene 28 and 2D SiC, 29 are intrinsically nonmagnetic but become magnetic when they are cut into one-dimensional nanoribbons with zigzag edges.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of photocurrents in systems lacking spatial inversion symmetry, known as the photogalvanic effect (PGE), was first proposed by Ivchenko and Pikus 19 and Belinicher, 20 and observed in conventional semiconductors in experiment by Asnin 21 and others, and has been explored extensively by researchers since then. [22][23][24][25][26][27][28][29] In recent years, with the rise of two-dimensional (2D) materials and their use in nanoscale electronics, [30][31][32][33] the interest of PGE in photocurrent generation has also started to arise in 2D systems. Actually, pure spin currents induced by PGEs have been predicted in certain twodimensional systems which are spin-polarized and lack spatial inversion symmetry.…”
Section: Introductionmentioning
confidence: 99%